2021
DOI: 10.1002/adsc.202001433
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthesis of α‐Trifluoromethylated Pyridines Based on Regioselective Cobalt‐Catalyzed [2+2+2] Cycloaddition using Trifluoromethylated Diynes with Nitriles

Abstract: Regioselective cobalt-catalyzed [2 + 2 + 2] cycloaddition using fluorine-containing diynes with nitriles was described. Cycloaddition of fluorinated diynes with nitriles under the influence of CoCl 2 (phen), zinc bromide, and zinc dust in dichloroethane at 80°C for 3 h took place smoothly, exclusively affording the corresponding α-fluoroalkylated pyridines in excellent yields. In addition, dinitriles as substrate were also found to be suitable for this reaction, giving the corresponding fluoroalkylated bipyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…Fluoroalkylated pyridines were obtained in 47-99% yield (Scheme 68). 130 A similar result was observed for the cyclization when a nonafluoroalkylated diyne was the partner instead of trifluoromethyl group. 2-Fluorinated pyridines were exclusively obtained when using a terminal alkyne.…”
Section: Review Synthesissupporting
confidence: 62%
See 1 more Smart Citation
“…Fluoroalkylated pyridines were obtained in 47-99% yield (Scheme 68). 130 A similar result was observed for the cyclization when a nonafluoroalkylated diyne was the partner instead of trifluoromethyl group. 2-Fluorinated pyridines were exclusively obtained when using a terminal alkyne.…”
Section: Review Synthesissupporting
confidence: 62%
“…However, 3-fluorinated pyridines could be obtained as the major isomer when a bulkier group on the alkyne was considered. 130…”
Section: Review Synthesismentioning
confidence: 99%
“…Konno and co-workers reported the construction of α-trifluoromethylated pyridine skeletons via the cobalt-catalyzed [2 + 2 + 2] cycloaddition reaction of trifluoromethylated diynes 102 with nitriles ( 103 or 104 ) (Scheme 22). 38 Despite the fact that they have already reported a similar work under the catalytic utility of rhodium with better scope and reactivity, with no added zinc halide, only trace amount of pyridine products was generated, indicating that zinc halides played a key role in this transformation. Besides, the authors found that the current method was also feasible with dinitriles 104 by increasing the loading amount of the Co-catalyst and zinc dust, yielding the desired dipyridine derivatives 106 in excellent yields.…”
Section: [2 + 2 + 2] Cycloaddition For the Synthesis Of Racemic Multi...mentioning
confidence: 99%
“…Subsequently, the chiral cyclonickel species 60 was formed by cyclometalation of alkynes with the cyano group promoted by zinc halides through intermediate 59 . 43 The intermediate 60 interacted with alkyne to give intermediate 61 , which underwent migration insertion with the coordinated alkyne to give a seven-membered cyclonickel species 62 . Finally, the pyridine 55 was generated upon reduction elimination along with the regeneration of the Ni catalyst.…”
Section: Nickel-catalyzed Asymmetric Cyclization Of Cyano–alkynementioning
confidence: 99%